Smart Shoe Rack with Face Recognition - Ansari, Aman; Kc, Gopal; Dhungel, Hasina (Journal of Electronics and Informatics, 2022)
The Smart Shoe Rack with face recognition is most likely one of the newest projects to have been introduced of its kind. In a Hindu country, temples are almost everywhere, inside the valley as well as outside, where one has to take off his footwear before entering. One of the most common yet overlooked problems is shoe misplacement in crowded temple areas. Therefore, to sort out this major problem, the idea of a Smart Shoe Keeping with face recognition has been proposed in this paper. By the use of microcontrollers, raspberry pi captures face encoding of a person and along with adjusting stepper motors, the shoe can be stacked at one of the sixteen different locations. The use of a clock helps in determining the stepper position at every instance. With face recognition technology, the shoes can be fetched. Once the face is recognized, it is matched with the previously captured person, and the system checks for the available shoe. The position of the stepper is then identified, and the shoe is fetched through the shortest path possible by the step anti/clockwise rotation of the stepper motor. The total time of storage of the footwear displayed in the LCD is then used for charging the amount of money accordingly.
Keywords: Recognition; microcontrollers; stepper motors; LCD; raspberry pi